PEMBUATAN BUBUK CABE MERAH MENGGUNAKAN VARIASI JENIS CABE DAN METODE PENGERINGAN (Jurnal Teknologi Pangan, 2013)
Chili powder is a product in the form of powder, practically in the preparation and have a long shelf life. This is the nature of the powder product having a very small particle size, has a  low  water  content.  Chili  powder  manufacturing  process were sorting,  washing  and  cleaning the stem, drying, milling and sieving. This study aims to find the best results from different  type of chili with different dryers include: Oven,  Freeze Dryer and  Cabinet dryer  on the quality of  red  chili  powder. Tthe  results  obtained  from  the  data  the  best  treatment  of  red  chili  powder using a freeze dryer  as follows: The water content of 15.8679%, β-carotene  318.728  IU, vitamin C 563.017 (mg/100g), color (L * 42.40; 20.25 b * 18.60) and organoleptic tests of color (83.5).Keywords : chili powder, cabinet drier, oven, freeze drier